Analisis Miskonsepsi Siswa Kelas XI SMA Negeri 1 Banawa Tengah Pada Pembelajaran Larutan Penyangga Dengan CRI (Certainty of Response Index) - Miftahul Jannah; Purnama Ningsih; Ratman Ratman (Universitas Tadulako, 2016)
The aim of this study is to analyze misconception of student in class XI SMA Negeri 1 Banawa Tengah on the buffer material. The type of this research is a description where the subject of research is 41 student. The instrument used was a multiple choice test with reasoned (CRI). It consists of 13 items which was accompanied by questionnaries. The results were obtained information that the students have misconceptions on subconcepts calculate pH buffer solution and way of working buffer solution, with amount of 37 students (46%). students at least experienced a misunderstanding on the component subconcepts buffer solution and way of working buffer solution with amount 17 student (21%). Furthermore, causes of student misconception is due to the lack of interest of student in the buffer solution material (22%), praconception and less understanding of the concept (80%), textbook of student (34%), and model of learning (57%). The result of this study shows that most of students in class XI SMA Negeri Banawa Tengah have misconception on the buffer material.